2004
DOI: 10.1002/art.20567
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased expression of macrophage elastase (matrix metalloproteinase 12) with rheumatoid arthritis

Abstract: Objective. Increased enzymatic activity of matrix metalloproteinases (MMPs) may promote the progression of rheumatoid arthritis (RA). We undertook this study to investigate the expression and localization of human macrophage elastase (MMP-12) in synovial tissue from RA patients and to compare MMP-12 levels in the synovial tissue and synovial fluid of RA patients with the corresponding levels in patients with osteoarthritis (OA).Methods. We obtained synovial tissues from 23 RA patients and 29 OA patients and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 15 publications
(23 reference statements)
1
57
0
5
Order By: Relevance
“…22 Although these results indicate that MMP-12 may be associated with RA, it is not clear whether MMP-12 directly participates in the pathogenesis of RA. In this study, we examined the hypothesis that increased MMP-12 potentially enhances the progress of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…22 Although these results indicate that MMP-12 may be associated with RA, it is not clear whether MMP-12 directly participates in the pathogenesis of RA. In this study, we examined the hypothesis that increased MMP-12 potentially enhances the progress of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 88%
“…22 To examine the hypothesis that MMP-12 may act as an important mediator in the pathogenesis of RA, we used MMP-12 transgenic (Tg) rabbits that specifically overexpress human MMP-12 only in macrophages and investigated the effect of overexpressed MMP-12 on the development of experimentally induced inflammatory arthritis. To the best of our knowledge, the present study provides the first evidence showing that MMP-12 up-regulation affects the process of inflammatory arthritis.…”
mentioning
confidence: 99%
“…Ample evidence has shown that in the synovial membrane of RA patients, the number of macrophages is correlated to the extent of joint destruction (Tak et al, 1997). Further, it has been demonstrated that synovial tissue and fluid obtained from patients with rheumatoid arthritis contained higher activity of MMP-12 (Liu et al, 2004).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…MMP-12, also called macrophage metalloelastase, was first identified as a potent elastolytic metalloproteinase specifically secreted by macrophages, 14,15 and increased activity of MMP-12 from inflammatory macrophages is associated with several destructive diseases, including emphysema, 16,17 rheumatoid and inflammatory arthritis, 18,19 skin diseases, 20 and abdominal aortic aneurysms. 21 In addition to elastin, MMP-12 also is able to degrade a broad spectrum of ECM components such as collagen type IV, fibronectin, laminin, vitronectin, proteoglycans, and plasminogen.…”
Section: Editorial P 1929 Clinical Perspective P 2001mentioning
confidence: 99%